The Stock Market Volatility and Regime Changes: A Test in Econometrics (Global Journal of Management and Business Research, 2017)
This paper applies the Markov switching hetero scedasticity model to stock return for India. The Markov switching model in our study takes into account the chance of regime shift, a possibility outside the purview of the GARCH model. Our finding tells us that the high variance of the transitory component tends to be short lived. Although parameters estimating the impact of time-varying expected returns and the delivery system are in some cases qualitatively different between the regimes, the differences do not produce significant changes in our model of stock returns.
Keywords: arch process; garch process; markov switching